(untitled) (Revista de Ciências Agroveterinárias, 2008)
Nitrogen affects directly pasture production in grasses. However, there is lack of information about nitrogen effect on the performance of cool season grass/legumes intercropped pastures. The objective of this work was to evaluate the effect of two levels of nitrogen fertilization on the production and botanical composition of a pasture constituted by black oat + ryegrass + vetch + arrow leaf clover. The work was conducted in three sites, one in Canoinhas and two in Major Vieira, Santa Catarina State, southern Brazil, during 2006. Treatments were arranged in a randomized block design, with three replicates on each site. Two levels of nitrogen fertilization were evaluated: 0 and 100 kg ha-1. Nitrogen was applied when black had two tillers. The nitrogen rate of 100 kg ha-1 in pasture of black oat + ryegrass + vetch + arrow leaf clover increased forage production and grass participation in the botanical composition. There was an increase of vetch and arrow leaf clover contribution with the evolution of forage cycle.